Mengungkap Tantangan Atlet Pemula dalam Menghadapi Tekanan Kompetisi - Gaffar, Asrul; Ahmad, Andika; Alamsyah, Syaiful; Sultan, Muh. Irzal; Anwar, Muh. Fauzan; Jariah, Ishak Ainul; Ramli, Irwandi Putra; Hafid, Erwan; Asriana, Asriana; Dewi, Aprilia Resky Surya (UNIVERSITAS NEGERI MAKASSSAR, 2022)
This study aims to identify and analyze the various psychological challenges faced by novice athletes in dealing with competitive pressure. The method used was a qualitative approach with a phenomenological study design, involving 24 novice athletes aged 16 to 20 years from various sports. Data were collected through semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results showed that novice athletes experience complex competitive pressures, including somatic anxiety, cognitive anxiety, social pressure, and fear of failure. The main factors causing this pressure are a lack of competitive experience, unrealistic expectations from the environment, and a lack of psychological support within the coaching system. The impact of this pressure not only affects physical performance but also the psychological well-being of athletes. This study suggests the importance of integrating sports psychology programs into youth athlete coaching curricula and the need for more systematic psychological support for novice athletes